2024
DOI: 10.3390/su16051854
|View full text |Cite
|
Sign up to set email alerts
|

New Coal Char-Based Building Products: Manufacturing, Engineering Performance, and Techno-Economic Analysis for the USA Market

Suraj Prasad Pandey,
Hua Yu,
Chooikim Lau
et al.

Abstract: Common building products, i.e., thin brick and stone veneer, add the look of brick walls or the enduring charm of natural stones into buildings and houses without imposing a substantial increase in structural load. This study investigates the mechanical strength, durability, and economic feasibility of producing innovative char-based thin bricks and stone veneers. The char-based thin brick vacuum treated with hydrophobic liquid exhibits water absorption rates within the 4–7% range, displays durability against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, the requirement for water absorption can be barely achieved as the optimum mix design CH30-TL4 has a water absorption of 4.63% which is near 5%. The research studies conducted by Pandey et al [33] have shown char as a porous material and have a direct influence on increasing water absorption [33]. They reported water absorption in the range of 4-7% for treated samples in a mix design containing 40% char [33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the requirement for water absorption can be barely achieved as the optimum mix design CH30-TL4 has a water absorption of 4.63% which is near 5%. The research studies conducted by Pandey et al [33] have shown char as a porous material and have a direct influence on increasing water absorption [33]. They reported water absorption in the range of 4-7% for treated samples in a mix design containing 40% char [33].…”
Section: Resultsmentioning
confidence: 99%
“…The research studies conducted by Pandey et al [33] have shown char as a porous material and have a direct influence on increasing water absorption [33]. They reported water absorption in the range of 4-7% for treated samples in a mix design containing 40% char [33]. So, paving blocks based on mix design CH30-T3 and CH30-TL3 can be used for light vehicular traffic areas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coal ash and desulfurization gypsum are waste products of coal mines and coal-fired power plants. One possible solution is to use bottom ash and fly ash as a partial or complete substitute for natural aggregates [9,10]. These materials are obtained at a minimal cost and are byproducts of coal processing, which is a more sustainable alternative to the resource-intensive processes involved in mining and processing natural aggregates.…”
Section: Introductionmentioning
confidence: 99%